MODERN EDUCATION THE HARMONY OF SPIRITUAL VALUES WITH INDEPENDENT THINKING AND CREATIVITY (World Bulletin of Social Sciences, 2025)
The article examines one of the priority directions of modern education—the cultivation of a freely and creatively thinking individual while preserving national and spiritual values, patriotism, and social responsibility. The author substantiates the necessity of not only developing independent thinking but also fostering education, spirituality, and collective consciousness in the educational process. The study proposes a balanced approach to nurturing a creative personality from both pedagogical and sociological perspectives.